International Diversification with Large- and Small-Cap Stocks - Eun, Cheol S.; Huang, Wei; Lai, Sandy (Journal of Financial and Quantitative Analysis, 2008)
Abstract To the extent that investors diversify internationally, large-cap stocks receive the dominant share of fund allocation. Increasingly, however, returns to large-cap stocks or stock market indices tend to comove, mitigating the benefits from international diversification. In contrast, stocks of locally oriented, small companies do not exhibit the same tendency. In this paper, we assess the potential of small-cap stocks as a vehicle for international portfolio diversification during the period 1980–1999. We show that the extra gains from the augmented diversification with small-cap funds are statistically significant for both in-sample and out-of-sample periods and remain robust to the consideration of market frictions.